2015
DOI: 10.1007/s12210-015-0396-3
|View full text |Cite
|
Sign up to set email alerts
|

Photonics and plasmonics go viral: self-assembly of hierarchical metamaterials

Abstract: Sizing and shaping of mesoscale architectures with nanoscale features is a key opportunity to produce the next generation of higher-performing products and at the same time unveil completely new phenomena. This review article discusses recent advances in the design of novel photonic and plasmonic structures using a biology-inspired design. The proteinaceous capsids from viruses have long been discovered as platform technologies enabling unique applications in nanotechnology, materials, bioengineering, and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 107 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…While the significant potential for virus-assisted plasmonic and photonic materials bottom-up assembly has been noted, 7,8 to the best of our knowledge, this is the first time that the possibility of an optical strain sensor based on a virus-like particle is discussed. Previous work aimed at expanding optical metamaterials research from structures fabricated in 2D planar geometries to bottom-up assembled 3D structures has shown that clusters of gold NPs can be encapsulated in an amphiphilic block copolymer shell.…”
Section: ■ Introductionmentioning
confidence: 89%
“…While the significant potential for virus-assisted plasmonic and photonic materials bottom-up assembly has been noted, 7,8 to the best of our knowledge, this is the first time that the possibility of an optical strain sensor based on a virus-like particle is discussed. Previous work aimed at expanding optical metamaterials research from structures fabricated in 2D planar geometries to bottom-up assembled 3D structures has shown that clusters of gold NPs can be encapsulated in an amphiphilic block copolymer shell.…”
Section: ■ Introductionmentioning
confidence: 89%
“…Understanding viral assembly pathways is critical to biology and biotechnology. In particular, virus-like particles (VLPs) have become attractive candidates for many applications in nano- and biotechnology, such as catalysis, gene therapy, and vaccination . One extensively studied virus for biological applications is the simian vacuolating virus 40 (SV40), a member of the polyomavirus family.…”
mentioning
confidence: 99%
“…Bacteriophage Qβ [190] and MS2 VLPs [164] have been reported as vehicles for the targeted delivery of light activated porphyrins, which upon photo-induction release singlet oxygen radicals into the cells for photodynamic therapy. Various other photochemical mechanisms have demonstrated controlled drug release from nanoparticles [184,192,193], and therefore represent valuable approaches to design VLPs for improved spatio-temporal control of drug release.…”
Section: Drug Releasementioning
confidence: 99%